Production of metal-organic framework-bearing polystyrene fibers by solution blow spinning. (10th August 2019) - Deneff, Jacob I.; Walton, Krista S.
Highlights: Solution blow spinning is evaluated as a method for creating MOF-polymer fibers. Polymer concentration has the largest effect on fiber morphology, texture, and size. Final diameter of the fiber is controlled by the viscosity of the solution. Nitrogen adsorption in the best composite shows 12% accessibility of the MOF. Composites are more accessible to CO2 and water vapor at 25 °C. Abstract: Solution blow spinning (SBS) is examined in this work as a platform method for creating MOF-bearing fiber composites for application in separations and catalysis. Composite fibers were produced from MOF suspensions in polymer solutions and examined for both MOF stability and accessibility. The composites were found to have more MOF accessibility than bulk polymers, but adsorption was hindered by the formation of a glassy polymer skin. The fibers were found to have better accessibility to water vapor and carbon dioxide at room temperature compared to nitrogen adsorption at 77 K, suggesting that they may be applicable for gases that have high permeability in the polymer. MOF-polymer fibers produced by SBS provide an interesting platform for delivery of different MOFs to target a variety of applications, particularly those requiring scale-up or in-situ production. Ultimately, this system combines a low-hazard, low-cost polymer and a highly stable MOF to enable a systematic evaluation of the effects of the process on the accessibility of active materials. Going forward, an examination of a broader set of polymers and MOFs is necessary to further characterize and optimize this method and to create and refine synergy between the MOF and the polymer.